Practice of Using a Training Session in the Form of a “Business Game” to Practice Actions When Establishing Levels of Terrorist Danger - A. V. Klushin (Управленческое консультирование)
This article informs of training as a form of «business game» for functioning regional contraterrorist commission of Russian Federation, as well estimation the certain level of terroristic threat for personal and authorities supposed to manage such a case. Some difficulties are being marked and ways to solve similar are shown. These training was used as an example in several regions of Russia and was a rather successful.